Transactions on Computational Science XVI - Gavrilova, Marina L.; Tan, C. J. Kenneth; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The LNCS journal Transactions on Computational Science reflects recent developments in the field of Computational Science, conceiving the field not as a mere ancillary science but rather as an innovative approach supporting many other scientific disciplines. The journal focuses on original high-quality research in the realm of computational science in parallel and distributed environments, encompassing the facilitating theoretical foundations and the applications of large-scale computations and massive data processing. It addresses researchers and practitioners in areas ranging from aerospace to biochemistry, from electronics to geosciences, from mathematics to software architecture, presenting verifiable computational methods, findings, and solutions and enabling industrial users to apply techniques of leading-edge, large-scale, high performance computational methods. The 16th issue of the Transactions on Computational Science journal contains 11 extended versions of selected papers from Cyberworlds 2011, held in Banff, AB, Canada, in October 2011. The topics span the areas of haptic modeling, shared virtual worlds, virtual reality, human-computer interfaces, e-learning in virtual collaborative spaces, multi-user web games, cybersecurity, social networking, and art and heritage in cyberspaces.
Function-Based Single and Dual Point Haptic Interaction in Cyberworlds -- Visual 3D Perception of Motion Environment and Visibility Factors in Virtual Space -- Continuous Control of Style and Style Transitions through Linear Interpolation in Hidden Markov Model Based Walk Synthesis -- Modeling and Analyzing the Human Cognitive Limits for Perception in Crowd Simulation -- Experiments in Artimetrics: Avatar Face Recognition -- Visualization of Joinery Using Homotopy Theory and Attaching Maps -- Example of Business Applications Using the Numerical Value and Exponential Calculation of the Cellular Data System -- Analysis of Inverse Snyder Optimizations -- Error-Controllable Simplification of Point Cloud -- Physically-Based Haptic Rendering for Virtual Hand Interaction -- The Advanced Open Metaplastic Platform for Cyber Art.
Keywords: Computer science; Computer Communication Networks; Information storage and retrieval systems; Artificial intelligence; Computer Science; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Computer Communication Networks; Computers and Society; Information Storage and Retrieval